TANGGUNG JAWAB HUKUM PENYELENGGARA PEER TO PEER LENDING TERHADAP RISIKO GAGAL BAYAR - Anissa Febriani; ' Pranoto (Fakultas Hukum Universitas Sebelas Maret, 2021)
Abstract This article aims to review the legal protection of lenders for the risk of default in the implementation of Fintech Peer to Peer Lending in terms of the coorporate legal responsibilities of Peer to Peer Lending. This research is a normative legal research that is prescriptive and applied and uses primary and secondary legal material sources. Data collection techniques in this study used the law approach and case approach. Data analysis techniques in this study used the syllogism and mindset method deductively. Legal problems that arise are in the form of weak legal protection for lenders when there is a risk of default, resulting in losses for the lender a nd weak regulations related to the implementation of Peer to Peer lending specifically on the role of the Peer to Peer Lending organizer in overcoming default risk. The solution to the problem of legal protection for the lender is in the form of efforts to maximize the legal responsibility of organizers of Peer to Peer Lending for its investors. Keywords: Legal Relationship; Legal Responsibility; Peer to Peer Lending Abstrak Artiel ini bertujuan untuk mengkaji perlindungan hukum bagi pemberi pinjaman terha dap risiko gagal bayar dalam penyelenggaraan Fintech Peer to Peer Lending yang ditinjau dari tanggung jawab hukum penyelenggara Peer to Peer Lending. Penelitian ini merupakan penelitian hukum normatif yang bersifat preskriptif dan terapan serta menggunakan sumber bahan hukum primer dan sekunder. Teknik pengumpulan data dalam penelitian ini menggunakan metode pendekatan undang-undang dan pendekatan kasus. Teknik analisis data dalam penelitian ini menggunakan metode silogisme dan pola pikir secara deduktif. Permasalahan hukum yang timbul yaitu berupa lemahnya perlindungan hukum bagi pemberi pinjaman saat terjadi risiko gagal bayar sehingga mengakibatkan kerugian bagi pihak pemberi pinjaman serta lemahnya regulasi terkait penyelenggaraan Peer to Peer lending tekhusus pada peran penyelenggara Peer to Peer Lending dalam mengatasi risiko gagal bayar. Solusi atas permasalahan perlindungan hukum bagi pihak pemberi pinjaman yaitu berupa upaya memaksimalkan tanggung jawab hukum penyelenggara Peer to Peer Lending bagi para investornya. Kata Kunci : Hubungan Hukum; Tanggung Jawab Hukum; Peer to Peer Lending